Pengaruh Disiplin Kerja, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan: Studi pada Karyawan CV. Indomitra Cipta Pangan - Ricky Putra Dwiyatsa; Setyani Dwi Lestari (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to determine the influence of Work Discipline (X1), Work Motivation (X2), and Work Environment (X3) on Employee Performance (Y) at CV. ABC. The sample in this study consisted of 51 employees of CV. ABC. Data were collected through questionnaires using a Likert scale, and the data were processed using Microsoft Excel 2019 and SPSS version 27 software. The sampling technique used was a saturated sampling method, where all employees in the company were selected as respondents. The research method applied in this study is multiple linear regression analysis, which allows for the identification of the relationships between independent variables (Work Discipline, Work Motivation, and Work Environment) and the dependent variable (Employee Performance). The results of the study indicate that the Work Discipline variable has a significant effect on Employee Performance, suggesting that employees who adhere to rules and regulations are likely to perform better. On the other hand, the Work Motivation variable does not have a significant effect on Employee Performance, indicating that motivation, in this case, may not play a major role in influencing performance. Furthermore, the Work Environment variable has a significant effect on Employee Performance, highlighting that a conducive and supportive work environment is crucial for improving employee performance. This study provides valuable insights into the factors that contribute to employee performance and can serve as a reference for improving human resource management strategies at CV. ABC.